HOT-CARRIER RELAXATION IN GAAS V-GROOVE QUANTUM WIRES - Maciel, A; Kiener, C; Rota, L; Ryan, J; Marti, U; Martin, D; Moriergemoud, F; Reinhart, F (1995)
We have measured hot carrier relaxation in GaAs V-groove quantum wires using time-resolved photoluminescence. Relaxation between confined one-dimensional subbands is clearly observed on the time scale of several hundred picoseconds. A simulation of the experiment using a hybrid multisubband Monte Carlo method which includes hot phonon and degeneracy effects gives good agreement with the measurements.© 1995 American Institute of Physics.